TASK-BASED LANGUAGE TEACHING: A PRACTICAL METHODOLOGY FOR ENGLISH LANGUAGE ACQUISITION - Jabborqulova , Xumora; Maxmatqulova , Nozima; Azimjonovna , Zaynab (Educational Research in Universal Sciences, 2023)
Task-based Language Teaching (TBLT) is a practical methodology that aims to facilitate the acquisition of the English language. This article provides an ABSTRACT overview of TBLT, exploring its principles and benefits in language learning.